2022
DOI: 10.1111/cts.13460
|View full text |Cite
|
Sign up to set email alerts
|

The impact of genetic variability in urate transporters on oxypurinol pharmacokinetics

Abstract: The genetic determinants of the allopurinol dose-concentration relationship have not been extensively studied. We aimed to clarify what factors, including genetic variation in urate transporters, influence oxypurinol pharmacokinetics (PKs).A population PK model for oxypurinol was developed with NONMEM (version 7.3). The influence of urate transporter genetic variants for ABCG2 (rs2231142 and rs10011796), SLC2A9/GLUT9 (rs11942223), SLC17A1/NPT1 (rs1183201), SLC22A12/URAT1 (rs3825018), SLC22A11/OAT4 (rs17300741)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…We have previously reported that Pacific Peoples have higher oxypurinol clearance, even after adjusting for body weight, kidney function and transporter variants (eg, ABCG2 and ABCC4). 21 The reason for this finding is not clear. Importantly, this work has not demonstrated differences for M aori (Indigenous New Zealanders) people in oxypurinol handing or Note: The doses are expected to achieve target serum urate concentrations <0.36 mmol L À1 in >80% of people with gout.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…We have previously reported that Pacific Peoples have higher oxypurinol clearance, even after adjusting for body weight, kidney function and transporter variants (eg, ABCG2 and ABCC4). 21 The reason for this finding is not clear. Importantly, this work has not demonstrated differences for M aori (Indigenous New Zealanders) people in oxypurinol handing or Note: The doses are expected to achieve target serum urate concentrations <0.36 mmol L À1 in >80% of people with gout.…”
Section: Discussionmentioning
confidence: 96%
“…A one-compartment pharmacokinetic model has been found to be a good fit for oxypurinol plasma concentrations in previous work. 20,21 Kidney function, body size and diuretic use have been consistently found to predict oxypurinol pharmacokinetics, 20,21 while recent work has additionally identified an ethnicity effect for selfreported Pacific Peoples. 21 On this basis, the recently published pharmacokinetic oxypurinol model from our group 21 was implemented verbatim.…”
Section: Population Pharmacokineticpharmacodynamic Modelmentioning
confidence: 99%
See 3 more Smart Citations